Native ornamentals of the sangam age - Kumar, C Subesh Ranjith (Indian Horticulture, 2019)
Plant wealth of any country can be characterized into wild (native) plants andexotic (plants by introduction) types. India is one of the rich biodiversity hotspots of the world, blessed with ample number of plants, many with ornamentalvalue. The biodiversity spots in India having wide range of plants with diverseadaptability, makes each and every state of the country a rich plant treasure.Tamil Nadu is the first state to have acquired the classical language status forits state language. Tamil has a rich cultural heritage, and is very unique inconserving and maintaining its rich plant diversity since Sangam age (200 BCto 300 AD). The Tamil Brahmi inscriptions deciphered during the recent pasthave established the contemporaneity of the inscriptions with the Sangamage. From the inscriptions, the association of plants with the people andplaces during that age is well informed. The mention of about 260 plantsshows the association of people in Sangam age with different places ofworld.